MARKETING STRATEGY FOR MSME HEALTH BEVERAGE PRODUCTS - Sri Sahbany; Irawansyah Irawansyah; Detty Agustin Riscal; Baiq Isti Hijriani; Jumari Ustiawaty; Andi Muhammad Aminullah; Nurul Khatimah Ismatullah; Adriyan Suhada (Politeknik Medica Farma Husada Mataram, 2023)
In Indonesia, you often find drinks labeled